IMPLEMENTATION OF BIG DATA ANALYTICS FOR BUSINESS DECISION MAKING IN E-COMMERCE - Farangiz Shuhratova Farhod qizi; Inomjon Qudratov; Dr. Maya Sar (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This paper seeks to investigate the role of Big Data Analytics in decision-making in the e-commerce field and the importance of their application, impacts and challenges faced in relation to the digital transformation era. Background of the study The background of the study refers to the rapid development of the e-commerce field in Indonesia where a vast volume of diverse and growing data is produced but not optimized in terms of its utilization in strategic decision-making. Methodology The study will be carried out using qualitative descriptive methodology which means the collection of secondary data through a literature study. Secondary data will be collected through a review of scientific journals, reference books, and scientific articles relating to the topic of investigation. Analysis The analysis will be performed to assess the application of Big Data Analytics and their importance in improving the performance of the business operation. In particular, this study seeks to explore the role of Big Data Analytics in consumer behavior analysis and data-based formulation of marketing strategies. Expected outcomes The study suggests that there exist many opportunities associated with the effective use of Big Data Analytics in decision-making and e-commerce operations in general. Particularly, the role of Big Data Analytics consists of faster decision making, increased efficiency, and deeper knowledge of consumer behavior and preferences. Efficient utilization of data also leads to product/service innovation, customer satisfaction, and enhanced competitiveness of e-commerce companies. Meanwhile, some challenges can be observed including massive volumes of data, difficulty of integration of data, data security and quality, and human resource availability with relevant analytic skills. Based on the results obtained, it is recommended to improve information technologies, implement data governance and data security policies and ensure efficient data management. Thus, the implementation of Big Data Analytics will become more effective and sustainable in the future.